Analysis of Improving Student Learning Outcomes and Activities in Thermochemistry Material Using the Teams Games Tournament (TGT) Learning Model Assisted by Wordwall Media - Rabiah Afifah Daulay; Abidah Ramadhani Nasution; Dira Khairunisa; Aralia Putri Marsyah; Artika Sardiana Dewi; Lia Yustina Manik; Elisabet Magdalena Manurung (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2026)
Thermochemistry is one of the chemistry topics that students often find difficult because it involves abstract concepts and mathematical calculations, resulting in low learning outcomes and limited classroom participation. This study aimed to improve students’ learning outcomes and learning activities through the implementation of the Teams Games Tournament (TGT) learning model assisted by Wordwall media in thermochemistry learning. The study employed Classroom Action Research (CAR) using the Kemmis and McTaggart model, consisting of two cycles: planning, action, observation, and reflection. The research was conducted in class XI-F1 of MAN 2 Model Medan during the 2025/2026 academic year, involving 35 students. Data were collected through achievement tests, observation sheets, and documentation. The results showed that the implementation of the TGT learning model assisted by Wordwall media improved students’ learning outcomes and learning activities. The average posttest score increased from 69.29 in Cycle I to 91.71 in Cycle II. Furthermore, the average N-gain score increased from 0.35 (medium category) to 0.87 (high category). Students’ learning activities also improved from 64% in Cycle I to 82% in Cycle II. These findings indicate that the integration of the TGT learning model and Wordwall media is effective in enhancing students’ understanding of thermochemistry concepts and encouraging active participation in the learning process.